Literature Study on the Potential of Rice Husk Ash as a Local Pozzolanic Material in Concrete - Nisa, Mitsaq Addina; Ansadilla Niar Sitanggang (Journal of Civil Engineering and Planning (JCEP), 2025)
The production of cement, as the primary material in concrete manufacturing, significantly contributes to global carbon emissions. To mitigate this impact, one of the solutions being developed is the use of natural or artificial pozzolanic materials as partial substitutes for cement. Rice Husk Ash (RHA) is an agricultural waste rich in amorphous silica and holds great potential as a local pozzolanic material in Indonesia. The review results show that using RHA in the range of 10–20% can enhance the compressive strength and improve concrete resistance to aggressive environments. The effectiveness of RHA is highly influenced by the fineness of its particles and the combustion process. Considering its availability and environmental impact, RHA has great potential as an eco-friendly material solution for construction based on local resources.